Toward economical purification of styrene monomers: Eggshell Mo2C for front‐end hydrogenation of phenylacetylene. Issue 8 (22nd April 2015) - Pang, Min; Shao, Zhengfeng; Wang, Xinkui; Liang, Changhai; Xia, Wei
<x xml:space="preserve">Abstract</x> An eggshell Mo2C catalyst which is designed from the rapid combination of molybdate with melamine is described. In contrast to Pd‐based catalysts, the eggshell Mo2C operates effectively with a wide‐concentration window in high‐temperature gas phase hydrogenation of phenylacetylene, thus, an economical and energy‐efficient front‐end purification of styrene monomers might be possible. © 2015 American Institute of Chemical Engineers AIChE J, 61: 2522–2531, 2015